Schutz’s Theory of Relevance: A Phenomenological Critique - Cox, R.R. author. aut Link
XI, 233 p.
Keywords: The following is neither exclusively the study of a philosopher nor a problem, and yet is both as well. Alfred Schutz is now recogniz ed to have been a profoundly insightful philosopher who explor ed the nature of social reality and the social sciences. His works are exercising a great influence in a wide range of problems and disciplines, the latter including the social sciences themselves. All of this is testimony to the sagacity and penetrating character of his analyses as well as the fruitfulness and soundness of his con cepts. Philosophy proceeds, however, by not merely accepting the work of great philosophers, but by engaging them in critical philosophic dialogue. It is time for this interchange to begin with respect to Schutz's work. To some extent, then, this work is di rected to that task. It does not undertake a systematic treat ment of the whole of Schutz's philosophy, for much more work in many aspects of his thought is yet to be done before such a pro ject can reasonably be undertaken. Yet, the issue of concern in this study is, I now believe, the philosophic center of the whole of Schutz's work.